Optimization Conditions for the Synthesis of 1,1’Bis-(4-Hydroxy Phenyl) Cyclohexane - Garchar, H.H.; Parsania, P.H. (Asian Journal of Chemistry, 2010)
The optimization conditions for the reaction between cyclohexanone (0.05 mol) and phenol (0.1 mol) in the presence of varying proportions of the mixture of hydrochloric acid and acetic acid (2 : 1 v/v) were determined in the temperature range 40–70ºC. The product was purifed from benzene and methanol (m.pt. 186ºC). For better yield (> 85%), the optimum catalyst concentration is 10 ml. The condensation time is considerably shortened by increasing the catalyst concentration.